German Scientific Diaspora Abroad (1933-1946): Mechanisms of Self-Organization and Instruments of Mutual Assistance - R. O. Reinhardt; G. N. Buslaev (Научный диалог, 2025)
This article examines the process of forming the German scientific diaspora abroad following the rise of the Nazis to power in 1933. It analyzes the factors leading to the large-scale emigration of scientific personnel from Germany, particularly focusing on the enactment of the Law for the Restoration of the Professional Civil Service on April 7, 1933. The study highlights a unique historical precedent in the establishment of a mutual assistance organization for scientists who were forced into exile — the Emergency Association of German Scientists Abroad. Emphasis is placed on the significance of personal initiative by prominent pathologist Philipp Schwartz and his close associates in founding this organization. The mechanisms and characteristics of its operations, key geographical areas of activity, and international connections are explored. Materials from a special archival collection of the British Society for the Protection of Science and Learning are analyzed. An assessment of the association’s effectiveness over its thirteen-year existence — from 1933 to 1946 — is conducted. The findings indicate that the organization founded by Philipp Schwartz played a crucial role in the institutionalization of the German scientific diaspora during this period, aiding nearly 1,800 scholars in escaping persecution by the Nazi regime. The legacy of the association is noted not only as a historical episode but also as a model of successful “scientific diasporic construction” under extreme conditions.